DEVICE FOR AUTOMATIC SOLAR PANEL CLEANING - H. D. Mamarasulova (Western European Studies, 2024)
This invention relates to automatic solar panel cleaning systems . A solar cell cleaning device that includes a power source connected to the solar cell, pollution control sensors, and wires located on the surface of the solar panel is characterized by the fact that the wires are made to vibrate and are connected together in a grid. An automated solar panel cleaning method has also been proposed. The invention provides effective cleaning of the surface of the solar cell from snow, ice, debris and other objects that interfere with the conversion of solar energy. Currently, the Earth's resources are running out, the environment is deteriorating every year, and modern energy sources contribute to this. Solar energy is a modern and effective alternative method of electricity production , which is evaluated by the very low prices compared to traditional energy types . Placing solar panels several kilometers above the ground in mountainous areas increases the flow of solar radiation , but complicates the maintenance and cleaning of solar panels. Therefore, creating an automated system for cleaning solar cells is an urgent task
Keywords: urgent; cleaning; automated; maintenance